COMPARISON OF THE REINFORCED CONCRETE BUILDING STRUCTURE WITH A CONVENTIONAL CONCRETE FLOOR PLATE AND KALSI FLOOR PLATE - ADRIANUS ZEGA (CV KULTURA DIGITAL MEDIA, 2020)
building using KALSI floor plates. The floor plate, which usually uses conventional concrete, can be replaced with a 20 mm thick KALSI floor product (Kalsi floor 20). In this research conducted an analysis of the behavior of the structure of the reinforced concrete building by using conventional concrete floor plate and Kalsi floor 20. The structure of the building model in this research is a four-story building structure and is designed following the regulation of SNI 2012. The evaluation of seismic behavior following the earthquake regulation of SNI 2013 is conducted by applying push load analysis (pushover analysis) using SAP 2000 software. The results of the study indicate the model drift ratio of concrete floor plate structure is smaller than the structure of the KALSI floor plate. The pushover analysis results show the level of performance of all structural models according to FEMA-356 / ATC-40 able to provide nonlinear behavior which is indicated by the initial phase of the majority of plastic joints on beam elements and beam sway mechanism. The performance level of the structure with conventional concrete slab includes at immediate occupancy level, while the performance level of the structure with with kalsi floor plate includes at life safety level.